Disruption of the MyoD/p21 Pathway in Rhabdomyosarcoma. (1997) - Weintraub, Michael; Kalebic, Thea; Helman, Lee J.; Bhatia, Kishor G.
Abstract : Purpose . Rhabdomyosarcoma (RMS) is an embryonal tumor thought to arise from skeletal muscle cells that fail to differentiate terminally. The majority of RMSs express MyoD, a protein essential to the differentiation of skeletal muscle. It was recently shown that during myogenesis, MyoD activates the expression of the cyclin-dependent kinase inhibitor (CDKi), p21, which itself plays a critical role in normal muscle development. To investigate the integrity of the MyoD/p21 pathway in RMS, we analyzed p21 and its relationship to MyoD expression in RMS. Methods . A panel of RMS samples was assembled from primary biopsies and from cell lines. Integrity of p21 was analyzed by single-strand conformation polymorphism (SSCP) and sequencing. Expression of p21 and MyoD was determined by Northern blot analysis, and the ability of exogenous p21 to arrest the cell cycle of RMS cell line was determined by transfection studies. Results . Our analysis indicates that although p21 is wild type in RMS, there is an inverse correlation between the levels of p21 and MyoD in these tumors. Tumors that express significant amounts of MyoD fail to express p21. This does not appear to be the result of mutations within the potential CACGTG sites present in the p21 promoter region or in the coding region of p21. An additional group of RMSs express very high levels of p21 but express little, if any, MyoD. Furthermore, RD, a RMS cell line which expresses high levels of endogenous p21, undergoes withdrawal from the cell cycle following forced expression of p21, suggesting that the pathway which would lead to G 1 arrest from endogenous p21 activity is defective. Discussion . These data suggest that the interaction between p21 and MyoD is defective in RMS although the precise nature of the defect remains to be elucidated.